Cobalt-catalyzed intermolecular hydroacylation of aldehydes: initiation of hydride transfer enables turnover. Issue 12 (11th May 2018) - Li, Ting; Xu, Bao-Hua; Zhu, De-Ping; Wang, Yao-Feng; Zhang, Suo-Jiang
Abstract : Intermolecular hydroacylation of aldehydes catalyzed by a low-valent cobalt system was developed. Mechanistic studies disclosed that the rate of the insertion step is significantly promoted in the presence of iPr2 NEt, which functions as an initiator of hydride transfer. Abstract : Intermolecular hydroacylation of aldehydes catalyzed by an in situ generated low-valent cobalt system was developed. Mechanistic studies disclosed that the desired hydroacylation was impeded by poor hydride donation by the respective Co(iii )–H phosphine complex formed by the oxidative addition of Co(i ) to the formyl C–H bond. Surprisingly, the reaction rate was significantly promoted in the presence of Lewis base N, N -diisopropylethylamine (iPr2 NEt) functioning as an initiator of hydride transfer, thereby offering an excellent reaction efficiency with high substrate tolerance.